A two-wave longitudinal study on the impacts of job crafting and psychological resilience on emotional labor. (September 2022) - Yang, Yong; Yan, Xiaohua; Zhao, Xinyuan (Roy); Mattila, Anna S.; Cui, Zhenzhen; Liu, Ziqi
Abstract: Based on the conservation of resource theory (COR), this study investigates the impacts of job crafting and psychological resilience on emotional labor and the mediating role of an individual's service orientation. A survey was conducted on more than 300 customer-contact employees in China using a two-wave longitudinal study. The results demonstrated that both job crafting and psychological resilience exerted a positive impact on customer focus and customer service under pressure. While customer focus exerted a positive impact on deep acting, customer service under pressure exerted a positive impact on both surface acting and deep acting. Customer focus and customer service under pressure mediated the correlation between job crafting and emotional labor (i.e., surface acting and deep acting). In addition, customer focus mediated the correlation between psychological resilience and deep acting.